Rancang Bangun Sistem Monitoring dan Kontrol Suhu Otomatis untuk Kandang Bebek Skala Kecil Menggunakan Internet of Things (IoT) - Alfatih, Gusti Zain; Amrulloh , Muhammad Faishol (JUKI : Jurnal Komputer dan Informatika, 2023)
Broiler ducks are a type of livestock duck whose growth is influenced by environmental temperature, so it is necessary to regulate the temperature of the cage to avoid a decrease in productivity and even the risk of death for livestock ducks. The enclosure temperature control system uses the Wemos D1 mini microcontroller, MF52A temperature sensor, fan / blower switch and incandescent lamp regulated by relay. If the measured temperature is above 33⁰C, the relay will be instructed by the microcontroller to turn on the fan/blower or turn off the light and if the measured temperature is below 31⁰C, the relay will be ordered to turn on the light or turn off the fan. From the research that has been carried out, an automatic temperature monitoring and control system for duck coops using internet of things (IoT) technology has been successfully created and works well according to the program set.